Dehydration risk factors and outcomes in older people in rural areas - Shaban Mostafa; Habib Nagat; Helmy Inas; Mohammed Huda Hamdy (Sciendo, 2022)
Objective: To determine the risk factors for dehydration in elderly people in one of Elbehira Governorate's villages.